Comparison of auditory brainstem response and electrocochleography to assess the coupling efficiency of active middle ear implants - Gawliczek, Tom; Mantokoudis, Georgios; Anschuetz, Lukas; Caversaccio, Marco D.; Weder, Stefan (Frontiers in Neurology, 2023)
Aim: This study aimed to compare the effectiveness of auditory brainstem response (ABR) and extracochlear electrocochleography (ECochG) in objectively evaluating the coupling efficiency of floating mass transducer (FMT) placement during active middle ear implant (AMEI) surgery.We enrolled fifteen patients (mean age 58.5 ± 19.4 years) with mixed hearing loss who underwent AMEI implantation (seven ossicular chain and eight round window couplings). Before the surgical procedure, an audiogram was performed. We utilized a clinical measurement system to stimulate and record intraoperative ABR and ECochG recordings. The coupling efficiency of the VSB was evaluated through ECochG and ABR threshold measurements. Postoperatively, we conducted an audiogram and a vibrogram.In all 15 patients, ABR threshold testing successfully determined intraoperative coupling efficiency, while ECochG was successful in only eight patients. In our cohort, ABR measurements were more practical, consistent, and robust than ECochG measurements. Coupling efficiency, calculated as the difference between vibrogram thresholds and postoperative bone conduction thresholds, was found to be more accurately predicted by ABR measurements (p = 0.016, R 2 = 1 Gawliczek et al.